In vitro effect of low-level laser on odontoblast-like cells - Oliveira, C. F. [UNESP]; Basso, F. G.; Lins, E. C.; Kurachi, C.; Hebling, Josimeri [UNESP]; Bagnato, V. S.; de Souza Costa, C. A. [UNESP] (Wiley-v C H Verlag Gmbh, 2011)
The aim of this study was to evaluate the metabolism of odontoblast-like MDPC-23 cells subjected to direct LLL irradiation. The cells were seeded (20,000 cells/well) in 24-well plates and incubated for 24 hours at 37 degrees C. After this period, the culture medium (DMEM) was replaced by fresh DMEM supplemented with 2 or 5% (stress induction by nutritional deficit) or 10% fetal bovine serum (FBS). The cells were exposed to laser doses of 2, 4, 10, 15 and 25 J/cm(2) from a near infrared InGaAsP diode laser prototype (LASERTable; 780 +/- 3 nm, 40 mW). One control group (sham irradiation) was established for each experimental condition (laser dose x FBS supplementation). Three and 72 hours after the last irradiation, cells were analyzed with respect to metabolism, morphology, total protein expression and alkaline phosphatase (ALP) activity. Higher metabolism and total protein expression were observed 72 hours after the last irradiation at the doses of 15 and 25 J/cm(2) (Mann-Whitney; p<0.05). Higher ALP activity was obtained with 5% FBS when the cells were irradiated with doses of 2 and 10 J/cm(2). For the dose of 25 J/cm(2), the highest ALP activity was observed with 10% FBS. It was concluded that the LLLT parameters used in this study stimulated the metabolic activity of the MDPC-23 cells, especially at the doses of 15 and 25 J/cm(2).
Keywords: phototherapy; odontoblast; lasers; cell metabolism